State-Society Relations in a Solidary Economy - Singer, Paul (2009)
This article looks at the Brazilian attempts to transform the Solidary Economy into a nationwide project that could be translated into public policy, planned and supported by the State. This is an economic project that presents itself as an alternative to the capitalist model, and thus looks towards the democratization of the economy, the substitution of competence for cooperation, and the expansion of political mechanisms for participation. The relationship between the State and diverse associations, such as social movements and civil society groups that are located in the realm of the Solidary Economy, is explored. Institutional spaces created for the negotiation of programmes, plans and objectives, between these multiple actors, will also be examined.